THINNING AND CLEANING EFFECT ON FORMATION OF NATURAL BEECH SAPLINGS IN TRANSCARPATHIA - Shyshkanynets, І. F. (Forestry and Forest Melioration, 2018)
An effect of intermediate felling of different intensity on the growth and formation of beech saplings has been determined. It is found that, in the age of thinning, felling intensity (depending on sapling density) may be very strong, strong, moderate and weak; and in the age of cleaning it is mainly average. At present, a stand normality is the assessment criterion for the intermediate felling in the age of lighting and cleaning. However, it is reasonable to use a stand density as such criterion.